The dark truth of question item designed for final set of examination paper in UiTM country side: An analysis of final set of examination paper / Mohd Ikhsan Md Raus ... [et al.] - Md Raus, Mohd Ikhsan; Sadjirin, Roslan; Sahri, Zulazeze; Abd Aziz, Muhd Eizan Shafiq; Zolkefley, Mohd Khairul Ikhwan (2013)
Decentralisation of UiTM final examination is one of the big agendas of UiTM in a near future. Decentralisation may take a long journey before everything is in a place. Therefore the paper aims to deliver and reveal some of the issues that need to be addressed and settled before and along the decentralisation process. One of the issues highlighted in this paper is the common mistake occurred in a question item designed of final examination paper. Interview and recommendation from the domain expert are also reported.